Effect Of Different Housing Systems On Biochemical Parameters In Buffaloes During Winter Season - R. A, Garkal; Kekan , P. M (Indian Journal of Veterinary Sciences and Biotechnology, 2014)
An experiment was conducted to study the effect of different housing systems on biochemical parameters in buffaloes during winter season. Twelve buffaloes were selected and randomly divided into two equal groups. Animals of group – A were housed in shed with net and animals of group – B to shed without net. There was significant (p<0.05) difference in THI between both the shed. The mean values of glucose and total cholesterol were significantly (p<0.01) higher in group A as compared to group B. Whereas, the mean values of total protein and globulin were non significantly higher, albumin and A:G ratio was non significantly lower in group A as compared to group B.